Nutrient Deficiencies of Landscape and Field-grown Palms in Florida - Timothy K. Broschat (EDIS)
This document describes the most common nutrient deficiencies of palms in Florida landscapes or field nurseries. See ENH1009 for fertilization recommendations for Florida landscapes and field nurseries. This document is ENH1018, one of a series of the Department of Environmental Horticulture, UF/IFAS Extension. Original publication date September 2005.